The Use of BIM Application for Schedule Planning and Real of Costs Estimation in Promenade Bridge Construction Project, Taman Mini Indonesia Indah - Ayisyah Herawati; Bilfiana Nuranisa; Risna Rismiana Sari; Ery Radya Juarti (Department of Civil Engineering, Politeknik Negeri Bandung, 2025)
Scheduling and cost estimation are essential for successful construction projects, including the revitalization of Taman Mini Indonesia Indah and the Promenade Bridge development. To improve efficiency and effectiveness, this study applies Building Information Modeling (BIM), using Tekla Structures 2022 for 3D modeling and Quantity Take-Off. The model provides detailed volume data, which—alongside daily and weekly reports—is used for cost analysis and scheduling. BIM integration enables better visualization, planning, and resource management throughout the project lifecycle. The result of the study shows that the total Real of cost estimation of Rp13.136.571.631,44 with the duration of work based on an analysis of daily reports and weekly reports for 155 working days starting on January 6th, 2021 until May 21st, 2021. The use of Tekla Structures supports accurate modeling and work volume calculations, helping streamline budgeting and scheduling processes. The use of Building Information Modeling (BIM) in construction projects significantly accelerates the scheduling and cost estimation process even though certain limitations must be considered during project planning and execution.